Reliability and Availability Analysis of Arepairable System With Two Types of Failure - M. A. El-Damcese; M. S. Shama (International Journal of Advances in Applied Sciences, 2015)
This paper investigates reliability and availability of a repairable system with two types of failure. Let failure rate and repair rate of [type1, type2] components are assumed to be exponentially distributed. The expressions of availability and reliability characteristics such as the system reliability and the mean time to failure are derived. We used several cases to analyze graphically the effect of various system parameters on the reliability system and availability system.